Students’ Perception on English Teacher’s Competences at SMK Negeri 1 Sawan - Tanjung, I Made Dwi Aryantara; Juniarta, Putu Adi Krisna; Mahendrayana, Gede (Jurnal Penelitian Mahasiswa Indonesia, 2022)
The purpose of this study was to investigate students’ perceptions of English teacher competences at SMK Negeri 1 Sawan. Pedagogy, personality, social, and professional competence were among the competencies assessed. The mixed method was used in this study. The data for this study were gathered quantitatively and qualitatively through the use of an online questionnaire and an interview guide. In the academic year 2020/2021, twelfth-grade students were given an online questionnaire. The questionnaire was completed by 152 students. The interviews were conducted with fifteen students. According to the findings of this study, students had 1) a positive perception of their English teacher’s pedagogy competence, 2) a very positive perception of their English teacher’s personality competence, 3) a positive perception of their English teacher’s social